Assessment of genetic and pheromonal diversity of the Cydia strobilella species complex (Lepidoptera: Tortricidae). (6th December 2012) - SVENSSON, GLENN P.; WANG, HONG‐LEI; LASSANCE, JEAN‐MARC; ANDERBRANT, OLLE; CHEN, GUO‐FA; GREGORSSON, BERIT; GUERTIN, CLAUDE; HARALA, EEVAMARIA; JIRLE, ERLING V.; LIBLIKAS, ILME; PETKO, VLADIMIR; ROQUES, ALAIN; et al.
<x xml:space="preserve">Abstract</x> Combining pheromone trapping and genetic analyses can be useful when trying to resolve complexes of closely related insect taxa that are difficult to distinguish based on morphological characters. Nearctic and Palearctic populations of the spruce seed moth, Cydia strobilella L., have been considered taxonomically synonymous since 1983, but more recent work revealing distinct sex pheromones for Canadian and Swedish moths suggest that populations in the two regions belong to different species. In order to test this hypothesis, we performed field trapping using different pheromone lures at ten sites in North America, Europe and Asia, and reconstructed phylogenetic relationships among trapped moths using mitochondrial (cytochrome oxidase subunit I) and nuclear (elongation factor 1 alpha) DNA sequence data. Trapping data and tree topologies for both genes revealed distinct pherotypes in North America and Eurasia. A genetically distinct population from China was investigated further with respect to its sex pheromone. Electrophysiological data indicated that Chinese females produce a deviant ratio of the sex pheromone components (dienic acetates) compared to Swedish females. However, trapping experiments in both areas revealed a similar broad response profile in males to a wide range of acetate ratios, and these populations should be considered taxonomically synonymous. A previous suggestion of an agonistic effect on the attraction of C. strobilella males in Sweden when adding the corresponding alcohols to the binary acetate blend was also tested in Sweden as well as in China, with no observed effect on attraction of males. In conclusion, our study demonstrates the great potential of using pheromone trapping as a tool for identification and delimitation of taxa within cryptic species complexes. Based on our data, Nearctic and Palearctic populations of C. strobilella should be considered different species, and C. youngana Kearfott stat. rev. is resurrected here as valid name for North American populations, which was the case before the revision in 1983.